2016
DOI: 10.1039/c6nr04091h
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small lipid–polymer hybrid nanoparticles for tumor-penetrating drug delivery

Abstract: Lipid-polymer hybrid nanoparticles, consisting of a polymeric core coated by a layer of lipids, are a class of highly scalable, biodegradable nanocarriers that have shown great promise in drug delivery applications. Here, we demonstrate the facile synthesis of ultra-small, sub-25 nm lipid-polymer hybrid nanoparticles using an adapted nanoprecipitation approach and explore their utility for targeted delivery of a model chemotherapeutic. The fabrication process is first optimized to produce a monodisperse popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 47 publications
0
58
0
Order By: Relevance
“…(Fang et al, 2010) The absorbance of NP(Ei→Dox) in FBS at 560 nm was reported to be suitable for detecting the formation of NP aggregates. (Dehaini et al, 2016; Fang et al, 2010; Hu et al, 2011) If NPs were not stable in FBS, then the aggregation of NPs would be detected by the increment in absorbance at 560 nm. The absorbance value stayed almost the same for 4 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(Fang et al, 2010) The absorbance of NP(Ei→Dox) in FBS at 560 nm was reported to be suitable for detecting the formation of NP aggregates. (Dehaini et al, 2016; Fang et al, 2010; Hu et al, 2011) If NPs were not stable in FBS, then the aggregation of NPs would be detected by the increment in absorbance at 560 nm. The absorbance value stayed almost the same for 4 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After the addition of β‐CD into the micellar solution to cap the biotin ligands on the surface of micelles via the host–guest interaction between β‐CD and biotin, there is no significant change in particle size. Due to the suitable size, these mixed micelles would be possible to avoid fast clearance by RES, which ensures passive targeting though the EPR effect before irradiation …”
Section: Resultsmentioning
confidence: 99%
“…Dehaini et al. prepared an ultra‐small LPHNPs using microfluidic‐based mixing method for targeted DTX delivery and showed improved tumor penetration and therapeutic efficacy compared to clinically approved formulation . Another method is the particle replication in non‐wetting templates (PRINT) technology developed to control particle shape, size, surface modification, physiochemical composition, and large‐scale fabrication .…”
Section: Nanocarriersmentioning
confidence: 99%